Anxiety and depression among Black breast cancer survivors: Examining the role of patient-provider communication and cultural values. Issue 7 (July 2022) - Lake, Paige W.; Conley, Claire C.; Pal, Tuya; Sutton, Steven K.; Vadaparampil, Susan T.
Abstract: Objective: Breast cancer survivors frequently experience anxiety and depression post-treatment. Patient-provider communication and cultural values may impact these psychological outcomes. We examined the impact of patient-provider communication and cultural values on anxiety and depression among Black breast cancer survivors. Methods: Using an observational, cross-sectional design, 351 survivors self-reported patient-provider communication (quality, confidence), cultural values (religiosity, collectivism, future time orientation), anxiety, and depression. Patients were categorized into high, moderate, and low levels of communication and cultural values. Separate linear regressions examined the effect of levels of communication and cultural values on anxiety and depression, controlling for sociodemographic variables. Results: A subset of breast cancer survivors reported clinically significant symptoms of anxiety (40%) and depression (20%). Communication was associated with anxiety (β = −0.14, p  = 0.01) and depression (β = −0.10, p  = 0.04). Specifically, women reporting higher levels of communication quality/confidence reported lower levels of anxiety and depression. There was a trend towards a significant association between cultural values and depression (β = −0.09, p  = 0.06). Conclusions: Black breast cancer survivors experience poor psychological functioning. Effective patient-provider communication may reduce anxiety and depression post-treatment. Practice implications: Patient-provider relationships and patient empowerment may be key components of cancer survivorship. Special attention should be paid to patient-centered communication for Black breast cancer survivors. Highlights: Black breast cancer survivors had low anxiety and depression post-treatment. A subset reported clinically significant symptoms of anxiety and depression. Better patient-provider communication predicted lower anxiety and depression. We assessed cultural values: religiosity, collectivism, and future time orientation. Cultural values were not associated with anxiety or depression.